Recent Advances for the Synthesis of N‐Unsubstituted Pyrroles. Issue 48 (22nd December 2021) - Efimov, Ilya V.; Kulikova, Larisa N.; Miftyakhova, Almira R.; Matveeva, Maria D.; Voskressensky, Leonid G.
Abstract: Pyrroles are an interesting class of heterocyclic compounds due to their widespread use both in medical chemistry and in the chemistry of new materials. Search and development of new effective methods for the synthesis of the pyrrole ring is an urgent task. Along with this, the systematization of already known synthesis methods is an equally important task. Herein, we focused on the results of the synthesis of NH‐pyrroles that have been obtained since 2015. Abstract : N‐unsubstituted pyrroles are a special class of heterocyclic compounds, the synthesis of which is widely presented in the literature. In this review, we have combined different synthetic protocols/methodologies exclusively for the synthesis of N‐unsubstituted pyrroles since 2015.